An antibody‐free strategy for screening putative HDM2 inhibitors using crude bacterial lysates expressing GST‐HDM2 recombinant protein. Issue 7 (4th June 2013) - Costa, Barbara; Grillone, Agostina Francesca; Salvetti, Alessandra; Rocchiccioli, Silvia; Iacopetti, Paola; Daniele, Simona; Da Pozzo, Eleonora; Campiglia, Pietro; Novellino, Ettore; Martini, Claudia; Rossi, Leonardo
<x xml:space="preserve">Abstract</x> Targeting the interaction of p53 with its natural inhibitor MDM2 by the use of small synthetic molecules has emerged as a promising pharmacological approach to restore p53 oncosuppressor function in cancers retaining wild‐type p53. The first critical step in the experimental validation of newly synthesized small molecules developed to inhibit MDM2‐p53 interaction is represented by the evaluation of their efficacy in preventing the formation of the MDM2‐p53 complex. This can be achieved using the in vitro reconstructed recombinant MDM2‐p53 complex in cell‐free assays. A number of possible approaches have been proposed, which are however not suitable for screening large chemical libraries, due to the high costs of reagents and instrumentations, or the need of large amounts of highly pure recombinant proteins. Here we describe a rapid and cheap method for high‐throughput screening of putative inhibitors of MDM2‐p53 complex formation – based on the use of GST‐recombinant proteins – that does not require antibodies and recombinant protein purification steps from bacterial cell lysates. Copyright © 2013 John Wiley & Sons, Ltd.